2012
DOI: 10.1111/1758-2229.12001
|View full text |Cite
|
Sign up to set email alerts
|

Specific association between bacteria and buoyant Microcystis colonies compared with other bulk bacterial communities in the eutrophic Lake Taihu, China

Abstract: The diversity of buoyant Microcystis colony-associated, settling particle-associated and free-living freshwater bacteria in the eutrophic Lake Taihu in China was compared by the polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) of 16S rRNA genes and by clone library analysis. The cluster analysis of DGGE profiles revealed that the buoyant Microcystis colony associates collected in summer and winter were clustered together and were distinct from settling particle-associated and free-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 92 publications
10
34
1
1
Order By: Relevance
“…Proteobacteria was also abundant and dominated 08MCA with a relative abundance of 77%. Other studies have shown Proteobacteria as a significant fraction of bloom associated bacteria [9], [12], [13]. Alpha- , Beta- , Gamma- , and Deltaproteobacteria were all detected in all nine samples, but relative abundances varied.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Proteobacteria was also abundant and dominated 08MCA with a relative abundance of 77%. Other studies have shown Proteobacteria as a significant fraction of bloom associated bacteria [9], [12], [13]. Alpha- , Beta- , Gamma- , and Deltaproteobacteria were all detected in all nine samples, but relative abundances varied.…”
Section: Resultsmentioning
confidence: 57%
“…Thus, all these communities were highly specialized, and as there were major differences among communities, we conclude that they were affected by the phycosphere conditions created by cyanobacteria. Others have also observed the selection of specific bacterial species within the Microcystis phycosphere by comparing Microcycstis -attached bacteria (phycosphere bacteria) with other microbial communities living in the same aquatic ecosystem [11], [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, taken together with these studies, we speculated that species-specific relationships might exist in colonial Microcystis formation and their bacteria. Shi et al (2012) also found a specific relationship between colonial Microcystis and their assoicated bacteria living in the mucilage. In addition, Parveen et al (2013) showed a clear distinction between Microcystis-attached and freeliving bacterial communities.…”
Section: Discussionmentioning
confidence: 75%